Perencanaan dan Strategi Komunikasi Analisis Pesan Desain di Gereja Tapian Nauli Pada Muda-Mudi Dalam Konteks Penyuluhan - Septy Nurliana Sinaga; Raikhapoor Raikhapoor (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Visual design at the HKBP Tapian Nauli Church plays an important role in providing counseling to young people. The message conveyed tends to be more effective if the design elements are adjusted to the preferences of the young audience, such as the use of modern colors and typography. Based on the research conducted, it can be concluded that design has a strategic role in religious counseling at the HKBP Tapian Nauli Church, especially in conveying messages to young people. Design is used as a supporting media that not only attracts attention but also helps clarify the religious values ​​that are to be conveyed.